Large Retropharyngeal Abscess Associated with Cervical Spine Tuberculosis - Amit Agrawal; Vissa Santhi; Gali Prakash Vignan Kumar; Yashwanth Sandeep (Indian Journal of Neurosurgery)
The authors report a case of a 25-year-old man who presented with the history of neck pain and weakness of the right hand of 6-month duration. He had history of fever with evening rise in temperature, loss of weight, and cough. Radiologic investigations of the cervical spine showed collapse of the C5 vertebral body and partial destruction of the C4 and C6 vertebral bodies with kyphotic deformity and a large retropharyngeal hyperintense collection. The patient underwent drainage of the abscess, and the histopathology was suggestive of tuberculosis. He was started on antitubercular treatment and doing well at follow-up.